Influence of mechanical stress on biomass allocation in three species (Pachira aquatica Aubl., Sextonia rubra (Mez) van der Werff and Simarouba amara Aubl.) with contrasting posture control mechanisms - Barbara Ghislain; Sabrina Coste; Grégory Faure; Jocelyn Cazal; Jonathan Prunier; Bruno Clair (Annals of Forest Science)
Abstract Key message The posture control in Pachira aquatica, Sextonia rubra and Simarouba amara is achieved through contrasted mechanisms involving tensile stress in wood only, bark only or both. This study evidenced that the restoration of verticality does not imply an overall cost for trees but modifies growth kinetics and biomass allocation to organs and tissues, improving the posture control of the trees in the three species. Context All trees need a motor system to correct their position through the generation of asymmetric tensile stress around the stem, leading to active bending. In angiosperms, depending on the species, tensile stress is generated either in wood (tension wood), in bark or in both. Aims Here, we investigated how gravitropic stimuli (tilted stems without any movement) may affect growth and biomass allocation and whether this process depends on the posture control mechanism of the species. Methods Tree growth kinetics, final biomass allocation and wood and bark proportion, localisation and density were measured on young tilted plants and straight plants as controls. Pachira aquatica, Sextonia rubra and Simarouba amara were selected according to the location of their their motor system within bark only, wood only or both wood and bark, respectively. Results In response to tilting, trees from the three species increased their diameter and decreased their slenderness, but the total biomass (including stem and roots) was not different from that in the control trees, suggesting that reaction to artificial tilting does not imply a specific cost for the plant. However, the species exhibited strong differences in growth kinetics, in the amount and organisation of the tissues or in biomass allocation to different organs (root vs shoot, wood vs bark), adapted to the specificity of the posture control mechanisms and improving their motor function. Conclusion Whatever the posture control mechanism, uprighting does not modify the total biomass invested. However, allocation of biomass to different organs is strongly modified to obtain an efficient control of the posture.